1992
DOI: 10.1063/1.462165
|View full text |Cite
|
Sign up to set email alerts
|

Density functional Gaussian-type-orbital approach to molecular geometries, vibrations, and reaction energies

Abstract: We present the theory, computational implementation, and applications of a density functional Gaussian-type-orbital approach called DGauss. For a range of typical organic and small inorganic molecules, it is found that this approach results in equilibrium geometries, vibrational frequencies, bond dissociation energies, and reaction energies that are in many cases significantly closer to experiment than those obtained with Hartree-Fock theory. On the local spin density functional level, DGauss predicts equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
412
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 941 publications
(428 citation statements)
references
References 56 publications
13
412
0
3
Order By: Relevance
“…Computation of bond energies is therefore one of the greatest concerns of quantum chemists. It was not until the 1980s that software implementations of HFS (and hence KS-DFT) were up to the task of computing accurate molecular energies, [26][27][28] but by the end of the decade robust programs were in place [36][37][38][39] and dissociation energies were under test. The energy required to dissociate a molecule entirely to free atoms, i.e., break all its bonds, is called "atomization" energy.…”
Section: Gradient Approximations: the Ascendency Of Dftmentioning
confidence: 99%
“…Computation of bond energies is therefore one of the greatest concerns of quantum chemists. It was not until the 1980s that software implementations of HFS (and hence KS-DFT) were up to the task of computing accurate molecular energies, [26][27][28] but by the end of the decade robust programs were in place [36][37][38][39] and dissociation energies were under test. The energy required to dissociate a molecule entirely to free atoms, i.e., break all its bonds, is called "atomization" energy.…”
Section: Gradient Approximations: the Ascendency Of Dftmentioning
confidence: 99%
“…For a wide range of systems DFT has been found to yield properties (geometries, dissociation energies, and frequencies) comparable in quality to the MP2 results (1 I). Also, it has been established that DFT yields accurate reaction energies for several chemical processes (12)(13)(14), when appropriate nonlocal gradient corrections are included. DFT is computationally less demanding than MP2 or other ab initio methods that include electron correlation, especially for large systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, all the quantum calculations on the structural optimizations, theoretical spectral characteristics, interaction energies with nH 2 and molecular orbitals have been performed using density functional theory (DFT) [25] and Becke's three-parameter exchange function [26] combined with the exchange functional component of Perdew and Wang (B3PW91) [27], 6-31G (d) basis set level. Datta and Pati have reported that the PW91 function provided more successful outcomes than B3LYP related physical adsorption of molecular hydrogen for circulene derivatives [28].…”
Section: Computational Detailsmentioning
confidence: 99%